Spinach hexokinase I is located in the outer envelope membrane of plastids - Sonnewald, Uwe; et al. (Febs Letters, 1999)
The subcellular localization of hexokinase activities in plant cells has been a matter of debate for a long time. We have isolated a hexokinase cDNA fragment from glucose-fed spinach leaves using a differential display reverse transcription-PCR approach. The corresponding cDNA was expressed in Escherichia coli and an antiserum, raised against the recombinant protein, was used in subcellular localization studies. The spinach hexokinase could be localized primarily to the outer envelope membrane of chloroplasts where it is inserted via its N-terminal membrane anchor. We suggest that the chloroplast envelope hexokinase is involved in the energization of glucose export from plastids rather than in the sugar-sensing pathway of the plant cell. (C) 1999 Federation of European Biochemical Societies.
Keywords: hexokinase; plant; glucose transport; plastid envelope membrane; sugar signalling; subcellular localization